As Bibliotecas e Arquivos e a nova lei orgânica do Ministério da Educação Nacional - BAD, Cadernos (Cadernos BAD, 1971)
As Bibliotecas e Arquivos e a nova lei orgânica do Ministério da Educação Nacional